A proposed theoretical framework for retinal biomarkers. Issue 1 (21st June 2022) - MacCormick, Ian James Callum; Zhang, Bo; Hill, Daniel; Cordeiro, Maria Francesca; Small, Dylan S.
Abstract: Objective: Propose a theoretical framework for retinal biomarkers of Alzheimer's disease (AD). Background: The retina and brain share important biological features that are relevant to AD. Developing retinal biomarkers of AD is a strategic priority but as yet none have been validated for clinical use. Part of the reason may be that fundamental inferential assumptions have been overlooked. Failing to recognize these assumptions will disadvantage biomarker discovery and validation, but incorporating them into analyses could facilitate translation. New theory: The biological assumption that a disease causes analogous effects in the brain and retina can be expressed within a Bayesian network. This allows inferences about abstract theory and individual events, and provides an opportunity to falsify the foundational hypothesis of retina–brain analogy. Graphical representation of the relationships between variables simplifies comparison between studies and facilitates judgements about whether key assumptions are valid given the current state of knowledge. Major challenges: The framework provides a visual approach to retinal biomarkers and may help to rationalize analysis of future studies. It suggests possible reasons for inconsistent results in existing literature on AD biomarkers. Linkage to other theories: The framework can be modified to describe alternative theories of retinal biomarker biology, such as retrograde degeneration resulting from brain disease, and can incorporate confounding factors such as co‐existent glaucoma or macular degeneration. Parallels with analogue confirmation theory and surrogate marker validation suggest strengths and weaknesses of the framework that can be anticipated when developing analysis plans. Highlights: Retinal biomarkers hold great promise for Alzheimer's disease (AD), but none are currently used clinically. Assumptions about the cause of retinal and brain changes are often overlooked, and this may disadvantage biomarker discovery and validation. We present a new approach to retinal biomarkers that describes cause and effect graphically in a Bayesian network. We show how this allows a more complete assessment of how well a biomarker might reflect the brain, and how data from right and left eyes can be used to rule out poor biomarker candidates.